Lip Balm Formulation and Physical Properties Evaluation Of Yellow Pumpkin Fruit (Cucurbita Moschata Duchesne) Ethanol Extract with Cera Alba Variation Concentration - Christiningtyas Eryani, Mikhania; Risky Ayu Paramita, Denok; Ayuning Trias, Diah; Husni, Patihul (Indonesian Journal of Pharmaceutics, 2024)
Lip balm is a cosmetic product generally used to care for, moisturize, decorate, and protect lips from environmental influences. This study aims to determine the effect of variations inconcentration of cera alba as base on the lip balm physical properties of yellow pumpkin fruit (Cucurbita moschata Duchesne)ethanol extract. The experimental design used was a pre-experimental one-shot case study. This study employed three formulas with varying concentrations of Cera alba, namely 10% (F1), 15% (F2), and 20% (F3). The physical properties of the lip balm under investigation included homogeneity, pH, adhesion, and hardness. The results showed that the variation concentration of cera alba had affect on adhesion and hardness, while not affect the homogeneity of physical properties and pH. Keywords : Yellow pumpkin, cera alba, lip balm